Digital Africa Summit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Organized by the Commonwealth Telecommunications Organisation (CTO), this conference will bring together speakers from Africa, international organisations and the investment community.